PENGARUH SISTEM INFORMASI AKUNTANSI, BUDAYA ORGANISASI, GAYA KEPEMIMPINAN, REWARD DAN SISTEM PENGUKURAN KINERJA TERHADAP KINERJA MANAJERIAL - Herlina Risnawati Sitorus; Arthur Simanjuntak; Duma Rahel Situmorang (Universitas Methodist Indonesia, 2022)
The purpose of this study is to consider whether accounting information systems, organizational culture, leadership style, rewards, and performance measurement systems can affect managerial performance and find out how much partial and simultaneous influence. Field studies carried out in data collection were using a questionnaire as a research tool which was distributed to the staff and employees of PTPN IV Pasir Mandoge Unit. Qualitative data is the data used in this study which will be quantified using a Likert scale, and converted into interval data. It can be concluded from the results of the partial analysis that the accounting information system variable (X1) has a positive and significant effect on managerial performance (Y), organizational culture variable (X2) has no effect on managerial performance (Y), leadership style variable (X3) has no effect on managerial performance (Y), reward variable (X4) has no effect on managerial performance (Y), performance measurement system variable (X5) has a positive and significant effect on managerial performance (Y). Based on the results of the simultaneous analysis, it is concluded that the effect of accounting information systems, organizational culture, leadership style, rewards, and performance measurement systems on managerial performance is 62.5%, and 37.5% is the influence of other variables not observed in this study.